Proteomic and structural comparison between cilia from primary ciliary dyskinesia patients with a DNAH5 defect - de Ceuninck van Capelle, Charlotte; Luo, Leo; Leitner, Alexander; Tschanz, Stefan A.; Latzin, Philipp; Ott, Sebastian; Herren, Tobias; Müller, Loretta; Ishikawa, Takashi (Frontiers in Molecular Biosciences, 2025)
IntroductionPrimary ciliary dyskinesia (PCD) is a genetic disorder affecting motile cilia across various organs, leading to recurrent respiratory infections, subfertility, and laterality defects. While several diagnostic tools exist—such as high-speed video microscopy, immunofluorescence staining, electron microscopy, and genetic screening—the relationship between different pathogenic variants within a single PCD gene and their effects on ciliary composition, structure, and clinical phenotype remains poorly understood.MethodsTo investigate this, we analyzed cilia from PCD patients with different mutations in axonemal dynein heavy chain dnah5 using mass spectrometry and cryo-electron tomography. These methods allowed us to examine both the protein composition and ultrastructural organization of motile cilia in affected individuals.ResultsThough all analyzed patients present similarly in traditional diagnostic methods, we observed differences in axonemal composition among patients carrying different dnah5 mutations. Specific reductions in ciliary components varied between individuals, indicating a mutation-specific impact. Notably, proteins such as VWA3B, KIAA1430/CFAP97, and DTHD1—not previously identified as components of human respiratory motile cilia—were detected in wild type cilia, but not in patient cilia. Lastly, we confirmed some changes in protein abundance in the 96-nm repeated unit of the axoneme between wild-type and PCD samples.DiscussionThese findings suggest that mutations in dnah5 result in varied and specific alterations in axonemal composition, reflecting the heterogeneity of the disease at the molecular level. The discovery of novel ciliary proteins and mutation-specific differences enhances our understanding of the complexity of PCD pathogenesis and may inform future diagnostic and therapeutic strategies.